Association of HCV Load and Interferon Therapeutic Response with Gender in Hepatitis C Patients Presenting to a Tertiary Care Health Facility, Rawalpindi - Mahnoor Javed Janjua , Mahnoor Javed Janjua (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: This Study was conducted to compare mean levels of quantitative PCR (RNA) of males and female Hepatitis C positive patients along with any disparity in responsiveness towards interferon therapy between males and females. Methods: This cross sectional analytical study was conducted from February 2015 to January 2016 at the Liver Centre of Holy Family Hospital, Rawalpindi, Pakistan. 204 patients of Hepatitis C, 104 males and 100 females were selected through Simple Random Sampling. The data was collected from the records of the patients regarding gender, HCV load, Quantitative PCR (polymerase chain reaction) to interferon, past surgical and transfusion history. Results: Mean PCR of females was 4.57E6± 1.998E7 IU whereas mean PCR of males was 3.04E6 ±8296048.199 and this difference was not statistically significant, (p=0.47). Among the males, 46.26% did not respond to the interferon treatment whereas those who responded were 34.69%. While among the females, 65.30% of did not respond to treatment and 34.70% responded, with a statistically insignificant difference (p=0.2). Conclusion: HCV load is unequivocally distributed amongst males and females. Females emerged as better responders to conventional pegylated 2 alpha interferon therapy than males. Key Words: HCV, viral load, interferon, response, gender, Polymerase Chain Reaction.